Cell wall remodeling under salt stress: Insights into changes in polysaccharides, feruloylation, lignification, and phenolic metabolism in maize - Oliveira, Dyoni M. (2020)
Although cell wall polymers play important roles in the tolerance of plants to abiotic stress, the effects of salinity on cell wall composition and metabolism in grasses remain largely unexplored. Here, we conducted an in-depth study of changes in cell wall composition and phenolic metabolism induced upon salinity in maize seedlings and plants. Cell wall characterization revealed that salt stress modulated the deposition of cellulose, matrix polysaccharides and lignin in seedling roots, plant roots and stems. The extraction and analysis of arabinoxylans by size-exclusion chromatography, 2D-NMR spectroscopy and carbohydrate gel electrophoresis showed a reduction of arabinoxylan content in salt-stressed roots. Saponification and mild acid hydrolysis revealed that salinity also reduced the feruloylation of arabinoxylans in roots of seedlings and plants. Determination of lignin content and composition by nitrobenzene oxidation and 2D-NMR confirmed the increased incorporation of syringyl units in lignin of maize roots. Salt stress also induced the expression of genes and the activity of enzymes enrolled in phenylpropanoid biosynthesis. The UHPLC–MS-based metabolite profiling confirmed the modulation of phenolic profiling by salinity and the accumulation of ferulate and its derivatives 3- and 4-O-feruloyl quinate. In conclusion, we present a model for explaining cell wall remodeling in response to salinity.